Human resource management factors and service recovery performance in Malaysian life insurance industry - Piaralal, Niriender Kumar; Mat, Norazuwa; Piaralal, Shishi Kumar; Bhatti, Muhammad Awais (Emerald Group Publishing Limited, 2014)
Purpose – The purpose of this paper is to investigate the human resource factors (rewards, training teamwork and empowerment) that affect service recovery performance (SRP) of customer service employees in life insurances companies.Life insurances industries in Malaysia are facing stiff competitions due to growing consumerism, changing consumer choices and expectations. SRP is very important aspect in the insurances firms toward retaining the customer and one of the key competitive advantages for sustainability and adding value to the organization in the future. Design/methodology/approach – The data obtained from 350 customer service employees based on convenience sampling were analyzed using regression and hierarchical analysis. Findings – There are two factors, namely, empowerment and training, affecting the SRP. The employment status moderated the relationship between reward and SRP.The limitations of this study have been noted and further research suggestions are also included that are very important for SRP. Originality/value – This study has added knowledge regarding the factors that affect SRP, in general, and precisely in life insurance industries in Malaysian context.